Teaching & Learning Tips 9: Case‐based teaching with patients. (7th June 2018) - Aluko, Ashley; Rana, Jasmine; Burgin, Susan
Abstract: Challenge : "Case‐based teaching" is a buzzword for engaging clinical teaching through cases, but how can it be implemented effectively in practice? We review popular case‐based teaching methods (i.e., one‐minute preceptor, SNAPPS, and the "Aunt Minnie method") for use during traditional one‐on‐one clinical preceptorships in the ambulatory dermatological setting.